Advanced in vitro evaluation of drug-induced kidney injury using microphysiological systems in drug discovery and development - Arakawa, Hiroshi; Matsushita, Kohei; Ishiguro, Naoki (Drug metabolism and pharmacokinetics, 2025)
Drug-induced kidney injury (DIKI) is a major cause of acute kidney injury (AKI). Given concerns about animal welfare and the need for more accurate prediction of human events, there is an urgent need to develop an in vitro evaluation method for DIKI using human cells. Renal proximal tubular epithelial cells (RPTECs) are the main targets of DIKI in drug discovery and development because of their abundant expression of drug transporters that contribute to renal-specific drug distribution. In general, physiological kidney function is significantly reduced in primary cell monolayer culture systems. However, with recent advances in cell engineering and regenerative medicine, human kidney-derived cell culture systems, with higher kidney function compared to conventional systems, have been established. For example, three-dimensional cultured RPTECs show enhanced expression of drug transporters and higher predictive performance than monolayer culture systems. The use of organs-on-a-chip with liver and kidney co-cultures also allows the detection of drug metabolite-induced nephrotoxicity. Kidney organoids differentiated from induced pluripotent stem cells (iPS) have also been established. In this review, we introduce a recently established renal cell culture system that includes a microphysiological system, and review the in vitro methods used to evaluate DIKI in RPTECs. [Display omitted]